Is employment-focused case management effective for patients with substance use disorders? Results from a controlled multi-site trial in Germany covering a 2-years-period after inpatient rehabilitation. Issue 1 (December 2016) - Saal, Susanne; Forschner, Lukas; Kemmann, Dietmar; Zlatosch, Jacqueline; Kallert, Thomas
Abstract Background Substance use disorders are associated with unemployment. An employment-focused case management (CMRE) has been conceptualised as a specific intervention to help substance use disorder patients return to competitive employment immediately after inpatient rehabilitation. This study investigated the effect of the intervention on return to work of persons with substance use disorders. Method The study was conducted in four German inpatient rehabilitation departments, and included unemployed patients (aged between 18 and 63 years) with a main clinical diagnosis of ICD-10 F10-19 disorders. Six weeks before discharge, patients were randomly allocated to CMRE or standard care (SC) using a quasi-randomised approach. The primary outcome measure was integration into competitive employment 24 months after discharge from rehabilitation. Secondary outcome domains were abstinence, duration of employment, proportion of publicly funded employment, satisfaction with life, precarious housing situation and precarious financial situation, and use of follow-up services. Outcome measures were assessed 6 weeks and 1–2 days prior to discharge, and 12 and 24 months after discharge from rehabilitation. Results One hundred sixty patients were allocated into the CMRE group and 160 patients into the control group. 267 resp. 179 participants could be included in the analyses performed for the 12-, and the 24-months follow-up assessments. At the study endpoint the rate of integration into the primary labour market was 35.6 % in the CMRE group and 41.2 % in the control group, respectively (Relative Risk 0.92, 95 % CI, 0.47; 1.79). There was a significantly higher proportion in the CMRE group, however, which immediately after discharge linked with services of the Federal Employment Agency or Job Centres. There were no statistically significant differences in other outcomes between the groups. Conclusions Compared to SC, the additional specific CMRE intervention did not result in superior effects on return to work rates, abstinence, satisfaction with life, and housing and precarious financial situation. But CMRE was more effective on linking substance use disorder patients with services of the Federal Employment Agency or Job Centres. Reasons for the finding that such close linking does not have an impact on return to work rates are discussed in detail. Trial registration Identifier:DRKS00003574 ; March 12, 2012. The trial was retrospectively registered.